Critical Discourse Analysis on TV Advertisements for Beauty Products - Falla Nour Rohmah; Suhardi Suhardi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
This research examines TV advertisements for beauty products on local TV from the perspective of Critical Discourse Analysis. This research mainly focuses on the use of language in beauty advertisements and the strategies used by advertisers to manipulate and influence their customers. This analysis is based on Fairclough's three-dimensional framework, which shows how the ideology of “beauty” is produced and reproduced through advertisements on TV. Qualitative research was conducted on beauty product advertisements from ten TV advertisements for beauty products in 2019. The advertisements taken and analyzed were advertisements for facial beauty products from various brands and types. The findings suggest that advertisers use a variety of strategies to manipulate women. Advertising language is used to control people's thoughts. The better the words the advertisers used to manipulate the viewers, the better reaction that they will get from the viewers. This research shows advertisers are not only promoting their products but highlighting society's standards of beauty and cultural values into the viewers’ lifestyle and how the TV advertisements have shaped the beauty ideology of social practice in Indonesia.